Integration of an UAV platform and SIMCom module to enable future UAV surveillance via a cellular network - Lee, Marc Yin Hua (2017)
Over the years, an increased usage of Unmanned Aerial Vehicles (UAVs), otherwise known as drones by the military have caught the attention of the commercial industry. The possibilities of using UAVs for commercial applications is vast, ranging from precision agriculture, inspection works and topographical mapping in construction, film and music production, to search and rescue missions, responding to natural disasters and local law enforcement, allowing for potential cost savings and risk at work. Furthermore, rapid advancement in manufacturing has enabled UAVs to be relatively cheaper models to be available in the market, allowing the use of UAVs for recreational purposes. Although rules and regulations have been put in place to keep the usage of UAVs in check, there are still concerns raised amongst Governments and Organizations worldwide. Therefore, in order to accommodate to the usage of commercial UAVs in the future, new surveillance technologies have to be created in order to keep the public and air space safe from UAVs. This research paper seeks to explore the possibilities of creating a surveillance system for UAVs, which involves the integration of UAVs and SIMCom modules, in hope that these UAVs can be integrated into the airspace through the use of cellular network as a means communicate UAVs and Unmanned Aerial Traffic Management (UTM) systems. Using Carl's Oswald Holmberg's project as a case study, improvements to the infrastructure and sequence of operations have been proposed. To showcase the research, a strong and stable communication link between the SIMCom module and UTM station was established via the cellular network to connect to a remote cloud server to transmit data. Furthermore, the overall design of the UAV has been improved to allow the UAV to be perform effectively and efficiently, while protecting its components from harm's way.